Comparative Study between Laparoscopic Assisted and Traditional Vaginal Hysterectomy (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: The choice of hysterectomy approach depends on the reason for hysterectomy, the overall health of the patient and surgeon’s experience. The choice of technique dictates hospital stay and healing time.Objective: To compare the efficacy and outcome of Laparoscopic Assisted Vaginal Hysterectomy (LAVH) and traditional Vaginal Hysterectomy (VH).Materials and Method: A total of 100 patients were purposively selected for this prospective comparative study during the period of January 2011 to January 2013 in CMH, Dhaka and Hitech Multicare Hospital. Non-malignant patients undergoing LAVH and VH by the same surgeon were included in this study. Clinical variables such as operative time, operative cost, blood loss, quantity of analgesics used and hospital stay were observed in both cases for comparison. Several other variables were also observed as postoperative complications such as amount of haemoglobin decrease, rise of temperature, urinary tract infection, vault granuloma in both the cases.Results:  There was no significant difference in terms of age, parity, body weight, uterine weight. The mean estimated blood loss in VH (100±32.8 ml) was significantly lower compared to LAVH (126.5±39.8 ml) group. Comparing the relief of post-operative pain, less analgesic was required, rapid patient recovery, and hospital stay time was less in LAVH group than VH group.Conclusion: LAVH is clinically beneficial in terms of less post-operative pain and less quantity of analgesia used, rapid patients’ recovery and shorter hospital stay than VH. It is useful for patients who prefer laparoscopy for cosmetic purpose.Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 29-31